GPS in Travel and Activity Surveys - Nielsen, Thomas S.; Hovgesen, Henrik Harder (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
The use of GPS-positioning as a monitoring tool in travel and activity surveys opens up a range of possibilities. Using a personal GPS device, the locations and movements of respondents can be followed over a longer period of time. It will then be possible to analyse how the use of urban spaces are embedded in the wider context of activity patterns (work, school etc.). The general pattern of everyday itineraries, including route choice and time spent at different locations “on the way” can also be analysed. If the personal GPS device is combined with an electronic questionnaire, for example in the shape of a Personal Digital Assistant (PDA) or cell phone, a whole new array of survey possibilities comes into being. Respondents can be asked to register their activities, evaluate or in other ways describe the attractiveness of places or modes based on their actual position and doings in the urban area. The paper presents the possibilities in travel and activity surveys with GPS and electronic questionnaires. Demonstrative mapping of test data from passive GPS registration of Copenhagen respondents is presented. The different survey possibilities given a combination of GPS and PDA based electronic questionnaires are presented together with a first generation PDA-based questionnaire.